Inequalities in compliance with the two-dose measles vaccination in Peruvian children aged 12 to 59 months in 2023 - Intimayta-Escalante, Claudio (2024)
Objective: The aim of this study was to evaluate sociodemographic inequities related to the coverage and compliance of the two-dose measles vaccination among Peruvian children in 2023. Materials and methods: An analytical cross-sectional study was conducted using data from a Demographic and Health Survey. Mothers aged 15 to 49 with children aged 12 to 59 months were included. Sociodemographic and health characteristics of these mothers were evaluated for inequity analysis using the Concentration Index (CI). This analysis was used to evaluate inequity in vaccination for first and booster doses against measles, and it was complemented with the Erreygers Concentration Index (ECI) and its decomposition. Results: Sixteen thousand, five hundred and twenty-six Peruvian mothers with at least one child aged 12 to 59 months were evaluated. Vaccination coverage was 85.7% and 54.4% for the first and booster doses, respectively. The coverage for both doses was 52.1%, and these figures decreased in people living in rural areas and the Amazon rainforest. In the inequity analysis, mothers with no education or only elementary schooling (ECI: -0.46), those living in the rainforest (ECI: -0.46), and those living in rural areas (ECI: -0.60) exhibited greater inequity in vaccination rates. The ECI was 0.04, and in their decomposition, some conditions, such as high school education, living in rural areas, and having health insurance, have a negative impact on vaccination inequity. Conclusion: Greater inequities in measles vaccination coverage were identified among Peruvian children aged 12-59 months whose mothers reside in rural or non-metropolitan areas of Lima, have lower education levels, and lack health insurance.